Daily Mail" Complete History of Formula One - Hill, Tim (Croxley Green Transatlantic, 2009)
Packed with more than 800 photographs, this book tells the story, year by year, behind 60 glorious years of Formula One. It features an extended final chapter on the battle for the 2009 championship and sets the scene for the 2010 season.
Include Colored Illustrations
Keywords: Grand Prix racing -- History -- Chronology